To solve the equation "x + (-6) = 12," you need to isolate the variable x by adding 6 to both sides of the equation. This cancels out the -6 on the left side, leaving you with x = 18. Therefore, the value of x that satisfies the equation is 18.
This could be intended as a trick question; the answer is 0. 0 + 6 = 12 - 6
X equals 6 ..
15 plus -3 equals 12 12 divided by -6 equals -2
yes. think of 6/12 plus 1/12. that is 7/12!
-18
it equals 72. just do 12 X 6
it equals 70
12
This could be intended as a trick question; the answer is 0. 0 + 6 = 12 - 6
X equals 6 ..
15 plus -3 equals 12 12 divided by -6 equals -2
6 + 6= 12
yes. think of 6/12 plus 1/12. that is 7/12!
27
6+6=12
18
-6